Effect of additive on the membrane perfomance and membran structure - Wong Ling Yong (Fakulti Sains dan Teknologi, 2012)
In order to prepare high performance of membrane filtration, an experiment using quaternary system was carried out with widely used membrane - Polyethersulfone (PES) as polymer, 7V-methyl-2-pyrrolidinone (NMP) as solvent, water as non-solvent, and polyvinylpyrrolidone (PVP) as additive.